Knoelle, a new monotypic wolf spider genus from Australia (Araneae: Lycosidae) - Framenau, Volker W. (Zootaxa, 2006)
A new monotypic wolf spider genus, Knoelle, is described to accommodate the Australian member of the Lycosinae Knoelle clara (L. Koch, 1877) comb. nov. as type species. Knoelle gen. nov. differs from all other wolf spiders in the peculiar structure of the male pedipalp. The tip of the cymbium carries a unique, large patch of macrosetae and the tegular apophysis has a unique lamellar structure between two hook-shaped processes. The median septum of the female epigyne widens distinctly anteriorly. Knoelle clara comb. nov. is common in the northern parts of Australia (New South Wales, Northern Territory, Queensland, Western Australia) north of ca. 30°S latitude. The species appears to prefer sandy, open to partly shaded habitats near freshwater, such as creeks, springs and lakes, but can also be found in sand dunes near beaches. Adults show a peak of activity in October (males) and November (females) and records of mature spiders are rare between May and August.